On the relationship between public health spending, governance and health outcomes: Evidence from Africa countries - HOUENINVO, GBODJA HILAIRE (My University, 2015)
The paper aims to reassess the public health spending-health outcomes nexus in the context of African countries. It emphasizes the interaction of governance with public health expenditure and its effects on health outcomes using a panel of 43 African countries from 1996 to 2012. The study uses cross sectional, fixed effects and Generalized Method of Moments (GMM) estimators, and find that health expenditure per capita and public spending has a significant impact on health outcomes. Moreover, the role of governance and its interaction with public health expenditure appear mixed. This result cannot be interpreted as governance has no impact on the effectiveness of public health spending. One explanation is that the real amount of resources and quality of institution may not perfectly reflect, respectively by public expenditure and governance indicators. The policy implications are discussed.
Keywords: Health expenditure; Governance; health outcomes; Panel data